Germplasm collection of rice in the State of Alagoas - Cruz dos Santos, Ana Lúcia; Queiroz, Fátima Maria; Gomes da Silva, Fernando (Pesquisa Agropecuaria Brasileira, 1997)
Rice (Oryza sativa L.) culture in Alagoas State, Brazil, is conducted by agriculturists that on their majority use primitives varieties. With the modernization of rice-growing these varieties have been substituted for new breedings. The objective of this work was to collect some rice germplasm in Alagoas State, in order to preserve the genetic variability of this material. The collection was done from july of 1992 to june of 1994 on some productive microregions of the State. It were collected 95 samples of the following varieties: Canarinho, Caianinha, Caiana Grande, Caiana Pequeno, Mineiro, 90 Dias, CICA-8, Amarelinho, Guape, Carolinda Branco, 450, Agulha, IR-8, Anão, Esave-36, Anãozinho, Jaguari, METICA 1, Vermelho, Macambira, Orizica, MG-1, EPEAL-101, EPEAL-102, CNA 4899, Agulhinha, Pé-de-Galinha, Amarelão, Canarinho Bico Roxo, Agulhão, Paulistinha, Vermelhão, Platinha and Chatinho.